Effect of Surfactants on Lansoprazole Solid Dispersions: A Pathway to Improved Dissolution and Development of Fast Disintegrating Tablets - Vijaya Laxmi, M.; Naik, Srinu; Yadav, Shashikumar; Vijaya Charan, G. (Journal of Neonatal Surgery, 2025)
Aim: The study aimed to enhance the solubility and dissolution rate of Lansoprazole, a poorly water-soluble drug, using binary and ternary solid dispersions (SDs) with polyethylene glycol (PEG) 6000 and surfactants such as Tween 80 and sodium dodecyl sulfate (SDS). Additionally, fast-disintegrating tablets (FDTs) were developed using optimized solid dispersions to improve drug release. Methods: Binary and ternary solid dispersions of Lansoprazole were prepared using the solvent-melt method. Physical mixtures were also formulated for comparison. These formulations were characterized through aqueous solubility studies, Fourier-transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and in vitro dissolution studies. The optimized solid dispersion was further incorporated into FDTs using different superdisintegrants. The FDTs were evaluated for pre-compression and post-compression parameters, including drug content, hardness, friability, disintegration time, and in vitro dissolution. Stability studies were conducted on the optimized formulation. Results: The ternary solid dispersion (SSD3) containing PEG 6000 and SDS significantly improved the solubility of Lansoprazole (3.12 mg/mL) compared to the pure drug (0.022 mg/mL). XRD analysis indicated reduced crystallinity in the solid dispersions, contributing to enhanced dissolution rates. The in vitro dissolution study revealed that SSD3 achieved 88.70% drug release in 60 minutes. Among the FDT formulations, F10, containing croscarmellose sodium (CCS), demonstrated the highest drug release (100%) within 40 minutes. Stability studies confirmed that F10 remained stable over six months with no significant deviation in drug content or dissolution profile. Conclusion: The study successfully demonstrated that ternary solid dispersions incorporating surfactants significantly enhance the solubility and dissolution rate of Lansoprazole. Furthermore, the optimized fast-disintegrating tablet (F10) formulation exhibited rapid drug release, making it a promising approach for improving the bioavailability of poorly water-soluble drugs.